Serotype Patterns of 2022 and 2023 Dengue Outbreaks In Chattogram, Bangladesh - Biswas, Rajat Sanker Roy; Sequeira, Austin; Hasan, Anamul; Zamil, Md Fahad; Alam, Mohammad Shafiul; Bishop, Jean (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Dengue viruses have been circulating in Bangladesh, including the Chattogram region, since 2000. This study aimed to investigate the dengue virus serotype patterns in Chattogram during 2022 and 2023. Materials and methods: The observational study was conducted at Chattagram Maa-O-Shishu Hospital between June and December 2022 and from October to December 2023. Patients who showed clinical signs of dengue and tested positive for the NS1 antigen were included. A total of 80 patients 68 in 2022 and 12 in 2023 underwent serotype testing. The 2022 samples were tested at SlieaGen L.L.C in Texas, USA, while the 2023 samples were analyzed at ICDDR’B in Bangladesh. Results: In 2022, 68 samples were tested via qPCR, with 27 (40%) testing positive for dengue. Of those, DENV-1 was found in 25 samples (36.8%) DENV-2 in 3 samples (4.5%) DENV-3 in 16 samples (23.6%) and DENV-4 in 1 sample (1.5%). The distribution showed that DENV-1 appeared alone in 10 samples (14.7%) DENV-3 and DENV-4 each in one sample. Co-infections were also seen: 12 samples (17.6%) had both DENV-1 and 3, and 3 samples (4.1%) had DENV-1, 2 and 3. In 2023, 12 samples were tested, with 10 (83.3%) testing positive for dengue. One sample had insufficient material and another was PCR-negative. Among the positives, DENV-2 was found in 9 samples (75%) and DENV-1 in 1 sample (8.3%). No co-infections were detected and DENV-3 and DENV-4 were not identified that year. Conclusions: All four dengue serotypes were present in Chattogram in 2022, with DENV-1 and DENV-3 being the most common. However, in 2023, the cases were primarily DENV-2, with a few DENV-1 cases. Notably, double and triple serotype co-infections were observed during the 2022 outbreak. There appears to have been a shift in dominant serotypes from DENV-1 in 2022 to DENV-2 in 2023. JCMCTA 2025 ; 36 (1) : 93-96